Endogenous antibody responses in REGN-COV2-treated SARS-CoV-2-infected individuals. Issue 1 (6th January 2023) - Kurshan, Ashwini; Snell, Luke B; Prior, Lucie; Tam, Jerry C H; Graham, Carl; Thangarajah, Rajeni; Edgeworth, Jonathan D; Nebbia, Gaia; Doores, Katie J
Abstract: Neutralizing monoclonal antibodies (mAbs) targeting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Spike glycoprotein have been developed for the treatment of COVID-19. Whilst antibody therapy has been shown to reduce the risk of COVID-19-associated hospitalization and death, there is limited understanding of the endogenous immunity to SARS-CoV-2 generated in mAb-treated patients and therefore ongoing susceptibility to future infections. Here we measure the endogenous antibody response in SARS-CoV-2-infected individuals treated with REGN-COV2 (Ronapreve). We show that in the majority of unvaccinated, delta-infected REGN-COV2-treated individuals, an endogenous antibody response is generated, but, like untreated, delta-infected individuals, there was a limited neutralization breadth. However, some vaccinated individuals who were seronegative at SARS-CoV-2 infection baseline and some unvaccinated individuals failed to produce an endogenous immune response following infection and REGN-COV2 treatment demonstrating the importance of mAb therapy in some patient populations.